IMPROVING THE LISTENING ACHIEVEMENT OF THE STUDENTS OF SMU NEGERI 1 SUNGGUMINASA THROUGH THE USE OF KANGGURU ENGLISH LEARNING PACKAGES - Syamsinar Syamsinar (Universitas Muhammadiyah Makassar, 2016)
The objectives of the research were to find out whether or not the use of KangGuru English Learning Packages can improve the listening achievement of the students of SMA Negeri 1 Sungguminasa in learning to listen. The research Pre-experimental method with one group pre-test and post-test design. The procedure of collecting data involved administering pre-test before treatment and then post-test. The population of this research was the eleventh year students of SMA Negeri 1 Sungguminasa, academic year 2015/2016 which consisted of 360 students. The sample was taken by random sampling technique, where the researcher took 4 students in every class and the total of the sample was 36 students. The result of the mean score of the students’ listening achievement before being taught through KangGuru English Learning Packages was 62,33 and it was classified as “fair”. Whereas, after doing the treatment, the mean score was 90,69 and it was classified was “very good”. To find out the significance of the difference between pre-test and post-test, the researcher applied t-test. The value of t-test was 11.57 which was greater than the value of t-table 1.689 at the level of significance 0.05 and the degree of freedom was 35. It was revealed that KangGuru English Learning Packages significantly improved the listening achievement of the students.Keywords: Listening, Achievement, KangGuru English Learning Packages.